The occupational safety and health in hospitals from the point of nurses [Zaštita na radu i zdravlje u bolnicama sa stajališta medicinskih sestara] - (:unkn) unknown (My University, 2009)
Hospitals have many forms of danger due to many different working conditions. Hospital personnel also take risks whilst providing health care which may cause health problems to themselves. The research, related to health and safety of nurses and other staff, was carried out in order to compare and determine the occupational health problems and evaluate the occupational safety precautions and applications of a private hospital accredited with JCI (Joint Commission International) and also a university hospital. The research took place amongst 162 nurses of a university hospital and 150 nurses of a private hospital, both in Istanbul, Turkey. The data was gathered between March and July 2007 using a survey consisting of 7 questions to find out the socio-demographic characteristics and 17 questions related to the occupational safety precautions and the occupational health problems of health personnel. According to the nurses, the safety applications and precautions of the private hospital were better than the university hospital. It was found out that the university hospital was poor at providing an ergonomic working environment and the private hospital was poor at planning the timetables of the nurses. In addition to this, - in both hospitals - sharp or pointed devices, blood/blood fluids and infected material were discovered to cause occupational diseases and other problems. In conclusion, the precautions and applications regarding occupational health and safety in the private hospital accredited with JCI were better than the university hospital.
Keywords: Health and safety; Hospital; Nursing